PENGARUH PENERAPAN MANAJEMEN RISIKO TERHADAP KINERJA KEUANGAN SEKTOR PERBANKAN PERIODE 2013-2017 - Deny Ismanto (Jurnal Fokus Manajemen Bisnis, 2020)
This study discusses liquidity risk, credit risk, operational risk, and interest rates risk on finance performance at the National Private Foreign Exchange Commercial Bank listed on the Indonesia Stock Exchange for the period 2013-2017. In this study, the independent variables are liquidity risk, credit risk, operational risk and interest rate risk and the dependent variable is financial performance. The object of research is the National Private Foreign Exchange Private Bank listed on the Indonesia Stock Exchange for the period 2013-2017. The population in this study was 23 banks. The sampling technique using purposive sampling method, based on research criteria, the research sample won 11 banks. The analysis tool used is panel regression data with eviews 6. The data used in this study is secondary data obtained from the official website pages of the Indonesia Stock Exchange and Bank Indonesia. Partially, the results of the study indicate that negative liquidity risk is not significant to finance, negative credit risk is significant to finance, operational risk is significantly negative to financial performance, and interest rates increase significantly positive to finance. Simultaneously liquidity risk, credit risk, operational risk and interest rate risk affect financial performance.